Hidden persuaders on film: Exploring young people's lived experience through visual essays. (21st September 2021) - Pick, Daniel; Hallsworth, Mary-Clare; Marks, Sarah
Abstract : page_382 other The Hidden Persuaders research group examines 'brainwashing' in the Cold War for the roles, real and imagined, played by psychologists, psychiatrists and psychoanalysts. Our project engaged young people in an exploration of the history of fears about brainwashing, and enabled them to explore their thoughts and ideas about the forces that shape their lives in contemporary society, through film-making. Working with three schools in the Camden area of London, our partners at the Derek Jarman Lab media hub, Birkbeck, University of London, and an artist facilitator (Lizzie Burns), we invited Year 12 students to learn filming and editing to create their own short video essays. The use of this format resulted in a significant depth of engagement and generated a wealth of creative responses. The various stages of the film-making process enabled the students to work out the terms of an argument and to consider how best to express it concisely. In the resulting films, they came up with a variety of forms of visual storytelling, and used the medium to express their thoughts, feelings and ideas in diverse ways, giving us a range of new perspectives which we could consider in relation to our historical research.